Gospel and mission in the writings of Paul an exegetical and theological analysis - O'Brien, Peter Thomas, 1935- (Grand Rapids, MI Baker, 1995)
Includes bibliographical references and index.
First published : Consumed by passion, 1993 ANZEA, Aust. [which see also]
Keywords: Bible. N.T. Epistles of Paul -- theology; Paul, the Apostle, Saint -- contributions in the theology of missions; Missions -- theory; Missions -- history -- early church, ca. 30-600.; Church history -- primitive and early church, ca. 30-600.